1997
DOI: 10.1046/j.1468-2982.1997.1705580.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Platelet Responsiveness in Migraine

Abstract: The aim of this study is to investigate whether oxidative stress may represent a pivotal determinant of the altered functional features of platelets in migraineurs during the headache-free period. Twenty-three patients with migraine with aura, free of attack, and 23 healthy volunteers were enrolled for the study. The involvement of an oxidative condition appears confirmed by the statistically significant increase (p < 0.001) of plasma levels of thiobarbituric acid-reactive substances which may be considered a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 21 publications
3
35
1
Order By: Relevance
“…Therefore, increased nitrosative-and oxidative stress may influence platelet function and cerebral microcirculation. Platelet secretory products released by activation of lipid peroxidation may impair cerebral blood flow (Tozzi-Ciancarelli et al 1997). It was suggested that NO may cause the headache through variations of cerebral blood flow by interacting with oxygen free radicals in migraine (Radomski et al 1991;Shimomura et al 1994;Ciancarelli et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, increased nitrosative-and oxidative stress may influence platelet function and cerebral microcirculation. Platelet secretory products released by activation of lipid peroxidation may impair cerebral blood flow (Tozzi-Ciancarelli et al 1997). It was suggested that NO may cause the headache through variations of cerebral blood flow by interacting with oxygen free radicals in migraine (Radomski et al 1991;Shimomura et al 1994;Ciancarelli et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested that reactive free radicals may be stimulated during migraine attacks in amounts sufficient to overcome normally effective protective mechanisms (Tozzi-Ciancarelli et al 1997). Malondialdehyde (MDA), one of the well-known secondary products of lipid peroxidation after exposure to reactive oxygen species and free radicals, may be used to evaluate oxidative damage (Esterbauer et al 1991;Karatas et al 2002).…”
Section: Platelet Isolationmentioning
confidence: 99%
“…Ex vivo platelet aggregation was performed within 30 min after blood collection as reported previously (Tozzi-Ciancarelli et al 1997). The platelet response was evoked by 0.25, 0.5, 1.0, and 2.0 lmolál ±1 ADP and collagen.…”
Section: Platelet Aggregation Analysismentioning
confidence: 99%
“…Thiobarbituric acid-reactive substances (TBARS), oxidative stress markers, have been found increased in plasma [24] and 24-h urine [3,4] of patients with migraine in headache-free periods, and urinary excretion was even more increased during migraine attacks [3]. Malonildialdehyde (MDA), a marker of lipid peroxidation, has been found increased [25,26] or decreased [2] in erythrocytes, and decreased in serum [2].…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione-peroxidase (GPx) has been found increased in erythrocytes [2] and normal in neutrophils [22], and catalase normal in erythrocytes [2] and neutrophils [22]. Nitric oxide (NO) has been found increased in 24-h urine of migraine patients during headache-free periods, both compared with normal controls or after the migraine-attack [24], decreased in serum [5], and increased in platelets during the migraineattack [26]. Finally, platelet peroxynitrite production has been found increased, and platelet membrane fluidity decreased in migraine patients during headache-free periods [23].…”
Section: Introductionmentioning
confidence: 99%